Outbreak Of Japanese Encephalitis In Sangli District, India. - ASAWARI SATHE; R.B. MUGADE; A.S. BHOSALE; MAHENDRA JAGTAP; T.V. SATHE (International Journal of Pharma and Bio Sciences, 2011)
A survey study of Japanese Encephalitis was conducted in Sangli district during the years 1997 to 2004. Five cases of JE were reported during the year 1997 and one case in year 2002. Various control measures such as spraying, fogging, biological control, piggary control and sanitization etc controlled the disease of the region. No incidence of Japanese Encephalitis was noticed after the year 2002. Details of outbreak of Encephalitis and its control measures were discussed in this paper.